Delusi Erotomania Tokoh Kanuma Dalam Novel Kankin Karya Akiyoshi Rikako - Nurilmi, Aqilah; Anwar, Fithyani; Kasmawati, Kasmawati; Nurfitri, Nurfitri (Universitas Hasanuddin, 2026)
This study aims to identify the characteristics of erotomanic delusion experienced by the character Kanuma in the novel Kankin by Akiyoshi Rikako using a literary-psychological approach. This research employs a qualitative descriptive method by analyzing narrative and dialogue excerpts that reflect the character’s behavior and thought patterns. The analysis is based on the theory of erotomania, also known as de Clérambault’s syndrome. The results show that Kanuma exhibits fixed-type erotomania, marked by a persistent belief in a romantic relationship with a single object. Kanuma believes that Yukie loves him and interprets ordinary interactions as signs of affection. Five characteristics are identified: persistent delusion, resistance to reality, obsessive behavior, complex interpretations, and potential for dangerous actions. The findings indicate that erotomania not only affects the perpetrator but also poses a serious threat to the victim.